Tackling the Impact of the COVID-19 Pandemic in Economy and Labour – a Case Studey of Serbia Regulation - Sovilj, Ranko P.; Stojković Zlatanović, Sanja N. (Medicine, Law & Society, 2021)
The paper deals with the foundation of policy and legal national framework addresses, particularly, the adequacy of state measures in the areas of economy and labour as a response to Covid-19 pandemic. The aim is, by analyzing recent soft law documents of international organizations and the introduced models of comparative policy practices, to make critical considerations regarding the policy responses in the crises conducted by the Serbian Government. The human-centered, holistic, and integrated approach had been applied accompanied by the legal normative and comparative methods. Putting the current Serbian regulation in the context of the international area of policy emergency response, the territorial approach has been determined as most applicable, accompanied by the spatial coverage to the most vulnerable sectors. Government stimulation policy in the area of economy and employment in the Covid-19 crisis must be based on the rapid and reliable assessment of the impact of a lockdown or trade and job restrictions as on medium to longer-term recovery strategies of trade and employment. The principle of global and national solidarity, public-private partnership are core elements that need to be incorporated in the legal framework to tackle the impact of the Covid-19 pandemics in the economy and labour.
Keywords: pandemic, state aid, set of socio-economic measures, economy and labour framework, Serbian Regulation